EFEKTIVITAS PEMANFAATAN APLIKASI CANVA SEBAGAI MEDIA PEMBELAJARAN BERDASARKAN KURIKULUM MERDEKA PADA MATERI TRANSFORMASI KELAS VII - Mahmuda Sumarno; Yulis Jamiah; Dona Fitriawan; Ahmad Yani T; Agung Hartoyo (Journal of Educational Review and Research, 2023)
This research is motivated by the need to use technology in education so that it can support the implementation of the independent curriculum which is currently being implemented. In addition, learning mathematics in transformation material requires visualization so that students can understand the teaching material well. Therefore, we need technology-based learning media that can support students' visualization abilities. In this case, the researcher wants to know and describe the effectiveness of using the Canva application as a learning medium for geometry transformation material for class VII at SMP Negeri 13 Pontianak. This study aims to describe the effectiveness of using the Canva application as a learning medium with the following indicators of effectiveness:1) the implementation of learning; 2) student learning outcomes; 3) student responses. This research is useful theoretically and practically for students, teachers, schools, and society. This research uses a qualitative-research where the results of the data will be analyzed descriptively. The research subjects of this study were class VII students at SMP Negeri 13 Pontianak. The object of this research is the effectiveness of using the Canva application as a learning medium based on the independent curriculum on transformation material. To obtain data, indirect observation techniques, measurement techniques and indirect communication techniques are used. The results of this study are that the use of the Canva application as a learning medium is said to be effective with indicators of good performance, indicators of learning outcomes that have passed classical completeness, and more than 70% of students have given positive responses